Implikasi Sikap Toleransi Dalam Rangka Meningkatkan Karakter Religius Siswa - Zulfa, Indana; Fatiya, Salwa; Fairuzy, Lulie Hana; Chandra, Rivanda Isnichaeni (Journal of Classroom Action Research, 2023)
This research contains the implications of students' tolerance attitudes. The aim of this research is to describe the influence of tolerant behavior in order to improve students' religious character. The research method used in this research is qualitative literature study research using data obtained through a literacy process from various books, articles and related journals using discussion. The second stage is data analysis. Data analysis was carried out using the content analysis method. The value of religious tolerance and the development of religious character is important because it has an impact on the growth of students' social behavior in the surrounding environment, especially at school. Through habituation activities, such as positive habits in the school environment such as setting a good example and motivating students, getting used to smiling, saying hello, getting used to learning tolerance through example, and getting used to providing activities, it is very possible to instill religious character and tolerance in the school environment